Preparation and Characteristic of PC/PLA/TPU Blends by Reactive Extrusion - Yueyun Zhou; Lifa Luo; Wenyong Liu; Guangsheng Zeng; Yi Chen (Advances in Materials Science and Engineering)
To overcome the poor toughness of PC/PLA blends due to the intrinsic properties of materials and poor compatibility, thermoplastic urethane (TPU) was added to PC/PLA blends as a toughener; meantime, catalyst di-n-butyltin oxide (DBTO) was also added for catalyzing transesterification of components in order to modify the compatibility of blends. The mechanical, thermal, and rheological properties of blends were investigated systematically. The results showed that the addition of TPU improves the toughness of PC/PLA blends significantly, with the increase of TPU, the elongation at break increases considerably, and the impact strength increases firstly and then falls, while the tensile strength decreases significantly and the blends exhibit a typical plastic fracture behavior. Meantime, TPU is conducive to the crystallinity of PLA in blends which is inhibited seriously by PC and damages the thermal stability of blends slightly. Moreover, the increased TPU makes the apparent viscosity of blends melt decrease due to the well melt fluidity of TPU; the melt is closer to the pseudoplasticity melt. Remarkably, the transesterification between the components improves the compatibility of blends significantly, and more uniform structure results in a higher crystallinity and better mechanical properties.